МОДЕЛЮВАННЯ ЕКОНОМІЧНОЇ ПОВЕДІНКИ ДОМОГОСПОДАРСТВ НА ОСНОВІ САМООРГАНІЗАЦІЇ ЇХ ЛОГІСТИЧНИХ СТРУКТУР (World Science, 2018)
The study considers some aspects of the formation and regulation of household economic behavior. It is shown that innovation-intellectual behavior is the main factor of self-organization of a household's activity. The conceptual approach to the definition of the structure of the logistic behavior of the household and the modeling of their self-organization is proposed.The theoretical basis of the proposed concept of modeling the economic behavior of households on the basis of the self-organization of their logistic structures should be a synergistic approach to the management and construction of mechanisms that can provide efficient functioning, sustainable development and economic security. A formal model can be represented as a system of divertial equations. The detailed structure of management of economic behavior of a household can be described by the tuple of parameters describing the set of elements of the system, the set of vectors of properties of elements of the system, the set of links between elements, the purpose and structure of the goals, the external environment.